Addressing Prevalence and Correlates Among a Sample of Egyptian University Students Who Suffer From Substance Use Disorders. (September 2018) - Bassiony, Medhat M.; Salah El-Deen, Ghada; Abdelghani, Mohamed; Youssef, Usama M.; Hassan, Mervat S.; El-Gohari, Hayam
Abstract : Background: Substance use is a public health problem among adolescents and young adults in Egypt. Objective: The objective of this study was to estimate the prevalence and correlates of substance use among Egyptian university students. Methods: This study randomly included 1176 (57.4% were male individuals) university students, with almost two thirds from practical course majors, with the remaining students from theoretical course majors. They answered a questionnaire of sociodemographic and clinical characteristics, which included the drug use disorders identification test, which was used to estimate student drug-related problems and dependence. Results: Lifetime substance use among students is 22.5%, with 156 (58.9%) demonstrating a polysubstance need, 221 (83.4%) using cannabis, 145 (54.7%) using tramadol, and 106 (40%) using alcohol. There is a significant association between substance use and older age, male sex, those in theoretical education, those living in an urban residence, and those who smoke cigarettes. In the group that used substances, currently, 114 (43%) experience drug-related problems and 43 (16.2%) experience dependence. Students with both issues are more likely to use alcohol, tramadol, or polysubstance than those without them; students with drug dependence are more likely to come from theoretical colleges, to smoke cigarettes, or to use substances at a younger age than those with drug-related problems. Conclusions: One in 5 university students used substances at least once in their lives. The most common included cannabis, tramadol, and alcohol, respectively. The risk factors for substance use were older age, male sex, urban residence, theoretical education, and cigarette smoking.